Kelimpahan Bintang Laut (Asteroidea) di Pantai Awang Kabupaten Lombok Tengah - Khairunnisah, Khairunnisah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This research aims to determine the abundance of starfish (Asteroidea) at Awang Beach, Central Lombok Regency. This type of research is exploratory descriptive. Using the quadrant transect method, sampling was carried out at three station points, namely station I, II and III. Data collection techniques include direct observation and documentation. The parameter measured is the abundance of starfish. The research results showed that the average value of the starfish abundance index at the three station points was 0.288 ind/m2, in the low category.